Dismenorea Pada Remaja Putri di Sekolah Menengah Atas - Sentia, Sahli; Asmariyah, Asmariyah; Destriani, Sri Nengsi; Dewiani, Kurnia; Kurniati, Neng (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2025)
Dysmenorrhea, or more commonly known as menstrual pain, is a complaint often experienced by teenage girls, specifically in the lower abdomen. Dysmenorrhea is a condition that has been known for quite some time, and it can be accompanied by nausea, vomiting, diarrhea, cold sweats, and dizziness. Some teenagers also experience pain in the lower back, waist, pelvis, and muscles down to the calves. The purpose of the research is to identify the factors associated with dysmenorrhea in adolescent girls at SMA Negeri 2 Kota Bengkulu. This study uses a cross-sectional design with a total of 51 female adolescent respondents. Data analysis was conducted univariately and bivariately using the Spearman rank test. This research was conducted at SMA Negeri 2 Kota Bengkulu with a total of 477 respondents, and the sample was selected using the accidental sampling technique, totaling 51 respondents. The results of the study on the relationship between Nutritional Status (BMI) and dysmenorrhea showed a p-value of 0.034 < 0.05, indicated by an r value of 0.297. There is a correlation between stress levels and dysmenorrhea with a p-value of 0.00 < 0.05, indicated by an r value of 0.495. There is no relationship between physical activity and dysmenorrhea, as seen from the p-value of (0.211) > 0.05. The conclusion is that there is a correlation between nutritional status (BMI) and dysmenorrhea, and stress levels, but no correlation between physical activity and dysmenorrhea.